Changes in Regional Ventilation during Treatment and Dosimetric Advantages of CT Ventilation Image-Guided Radiotherapy for Locally Advanced Lung Cancer - Yamamoto, Tokihiro (Int J Radiat Oncol Biol Phys, 2018)
PURPOSE/OBJECTIVE: Lung functional image-guided radiotherapy (RT) that avoids irradiating highly-functional regions has potential to reduce pulmonary toxicity following RT. Tumor regression during RT is common, leading to recovery of lung function. We hypothesized that computed tomography (CT) ventilation image-guided treatment planning reduces the functional lung dose compared to standard anatomical image-guided planning in two different scenarios with or without plan adaptation. METHODS AND MATERIALS: CT scans were acquired before RT and during RT at two time points (16–20 Gy and 30–34 Gy) for 14 patients with locally advanced lung cancer. Ventilation images were calculated by deformable image registration (DIR) of four-dimensional (4D) CT image datasets and image analysis. We created four treatment plans at each time point for each patient: functional adapted, anatomical adapted, functional unadapted, and anatomical unadapted plans. Adaptation was performed at two time points. DIR was used for accumulating dose and calculating a composite of dose-weighted ventilation used to quantify the lung accumulated dose-function metrics. The functional plans were compared with the anatomical plans for each scenario separately to investigate the hypothesis at a significance level of 0.05. RESULTS: Tumor volume was significantly reduced by 20% after 16–20 Gy (p=0.02) and by 32% after 30–34 Gy (p<0.01) on average. In both scenarios, the lung accumulated dose-function metrics were significantly lower in the functional plans than in the anatomical plans without compromising target volume coverage and adherence to constraints to critical structures. For example, functional planning significantly reduced the functional mean lung dose by 5.0% (p<0.01) compared to anatomical planning in the adapted scenario, and by 3.6% (p=0.03) in the unadapted scenario. CONCLUSIONS: This study demonstrated significant reductions in the accumulated dose to the functional lung with CT ventilation image-guided planning compared to anatomical image-guided planning for patients showing tumor regression and changes in regional ventilation during RT.